Comparison of Protein Carbonyl (PCO), Paraoxonase-1 (PON1) and C-Reactive Protein (CRP) as Diagnostic and Prognostic Markers of Septic Inflammation in Dogs - Beatrice Ruggerone; Donatella Scavone; Roberta Troìa; Massimo Giunti; Francesco Dondi; Saverio Paltrinieri (Veterinary Sciences, 2021)
Reliable diagnostic and prognostic markers of sepsis are lacking, but essential in veterinary medicine. We aimed to assess the accuracy of C-Reactive Protein (CRP), protein carbonyls (PCO) and paraoxonase-1 (PON1) in differentiating dogs with sepsis from those with sterile inflammation and healthy ones, and predict the outcome in septic dogs. These analytes were retrospectively evaluated at admission in 92 dogs classified into healthy, septic and polytraumatized. Groups were compared using the Kruskal–Wallis test, followed by a Mann–Whitney U test to assess differences between survivors and non-survivors. Correlation between analytes was assessed using the Spearman’s test, and their discriminating power was assessed through a Receiver Operating Characteristic (ROC) curve. PON1 and CRP were, respectively, significantly lower and higher in dogs with sepsis compared with polytraumatized and clinically healthy dogs (p < 0.001 for both the analytes), and also in dogs with trauma compared with healthy dogs (p = 0.011 and p = 0.017, respectively). PCO were significantly increased in septic (p < 0.001) and polytraumatized (p < 0.005) as compared with healthy dogs. PON1 and CRP were, respectively, significantly lower and higher in dogs that died compared with survivors (p < 0.001 for both analytes). Ultimately, evaluation of CRP and PON1 at admission seems a reliable support to diagnose sepsis and predict outcomes.